2016
DOI: 10.1007/s00382-016-3135-2
|View full text |Cite
|
Sign up to set email alerts
|

Projections of Southern Hemisphere atmospheric circulation interannual variability

Abstract: variance in the RCP8.5 experiment are an order of magnitude greater than for the internal components, indicating that the SH seasonal mean circulation will be even more dominated by a SAM-like annular structure. Across the three MMEs, there is convergence in the projected response in the slow-external component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Grainger et al (2017) [81] further showed that for SWWA, the negative trend in rainfall was closely associated with the aforementioned annular pattern in Z 500hPa geopotential height, with positive height anomalies and anti-cyclonic flow at 300 hPa over the region of decreasing rainfall. Frederiksen and Grainger (2015) [58] had earlier identified this same pattern in the leading slow external geopotential height mode of covariability in multi-model ensemble CMIP3 simulations and attributed this trend to external radiative forcing, including greenhouse gases.…”
Section: Projections Of the Future Sh Climatementioning
confidence: 95%
See 1 more Smart Citation
“…Grainger et al (2017) [81] further showed that for SWWA, the negative trend in rainfall was closely associated with the aforementioned annular pattern in Z 500hPa geopotential height, with positive height anomalies and anti-cyclonic flow at 300 hPa over the region of decreasing rainfall. Frederiksen and Grainger (2015) [58] had earlier identified this same pattern in the leading slow external geopotential height mode of covariability in multi-model ensemble CMIP3 simulations and attributed this trend to external radiative forcing, including greenhouse gases.…”
Section: Projections Of the Future Sh Climatementioning
confidence: 95%
“…They found that most models simulated the changes in zonal wind, but only about a third of the models captured the observed changes in baroclinic instability with reduced magnitude. The subset of models capable of simulating the observed spatial trends in the Phillips Criterion and the associated changes in winter rainfall over southern Australia, especially in SWWA, were used as a basis for a subsequent CMIP5 multi-model ensemble study conducted by Grainger et al (2017) [81]. They found that the externally forced austral summer (DJF) variability in the Z 500hPa geopotential height resided almost exclusively in an SAM-like teleconnection with uniform positive loading in the tropics, extending to at least 30 • S, exhibiting an annular structure with negative loadings at higher latitudes.…”
Section: Projections Of the Future Sh Climatementioning
confidence: 99%
“…They found that most models simulated the changes in zonal wind, but only about a third of the models captured the observed changes in baroclinic instability and with reduced magnitude. The subset of models capable of simulating the observed spatial trends in the Phillips' Criterion and the associated changes in winter rainfall over southern Australia and especially in SWWA were used as a basis for a subsequent CMIP5 multi-model ensemble study conducted by Grainger et al (2017) [76]. They found that the externally forced austral summer (DJF) variability in the Z 500hPa geopotential height resided almost exclusively in a SAM-like teleconnection with uniform positive loading in the tropics, extending to at least 30 • S with an annular structure with negative loadings exhibited at higher latitudes.…”
Section: Projections Of the Future Sh Climatementioning
confidence: 99%
“…By reducing the dimensionality of the data, the relationship between the atmospheric and surface weather may be more readily understood. Changes in atmospheric CPs have been linked with changes in atmospheric and oceanic phenomena such as the North Atlantic Oscillation (NAO; Saaroni et al ., 2019; Putniković et al ., 2018; Cherenkova and Semenov, 2017) the Arctic Oscillation (AO) via Arctic amplification (Francis et al ., 2018), the El Niño Southern Oscillation (ENSO; Grainger et al ., 2017), and the Atlantic Multidecadal Oscillation (AMO; Cherenkova and Semenov, 2017). Many of the studies that examine changes in the frequency of CPs are typically interested in better understanding how these changes are associated with extreme surface weather events.…”
Section: Introductionmentioning
confidence: 99%